FEATURES OF DNA REPAIR MECHANISMS IN HUMAN-INFECTING BACTERIAL PATHOGENS - Turgimbayeva , A.M.; Abeldenov, S.K.; Akhmetova , D.G.; Saparbayev , M.K.; Ramankulov , Y.M.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2017)
Studies on bacterial DNA repair mechanisms have historically been carried out in Escherichia coli as the model system. However, evidence is accumulating that DNA repair mechanisms in other bacterial species may differ fundamentally from those of E. coli. Pathogens such as Mycobacterium tuberculosis, Helicobacter pylori, and Staphylococcus aureus have evolved various DNA repair mechanisms that help them to persist. When bacterial pathogens enter the human body they are exposed to a range of host defense mechanisms, such as the formation of reactive oxygen species and reactive nitrogen intermediates that can induce mutations in their genomes. Bacterial infections can induce a range of pathogenic diseases, and each of the causative bacterial species has characteristic DNA repair mechanisms. The study of the functions and biological roles of DNA repair enzymes is very important for understanding bacterial persistence in the human body. Moreover, repair enzymes might be potentially new targets for therapeutic agents. In this study, the DNA repair mechanisms of various human pathogens are described.